2019
DOI: 10.1111/een.12767
|View full text |Cite
|
Sign up to set email alerts
|

Plant composition, not richness, drives occurrence of specialist herbivores

Abstract: 1. How herbivore plant diversity relationships are shaped by the interplay of biotic and abiotic environmental variables is only partly understood. For instance, plant diversity is commonly assumed to determine abundance and richness of associated specialist herbivores. However, this relationship can be altered when environmental variables such as temperature covary with plant diversity. 2. Using gall‐inducing arthropods as focal organisms, biotic and abiotic environmental variables were tested for their relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Some studies have considered only the host plant richness and a linear positive relationship between host plant and galling insect richness was also found (Araújo, 2011;Souza et al, 2016). Moreover, in agreement with the high specificity of galling insects to their host plants (Carneiro et al, 2009), the specific composition of these insect communities has been closely related to floristic composition (Julião et al, 2017;Knuff et al, 2019). The proportion of plants damaged by phytophagous insects was also used as an herbivory indicator (Ekholm et al, 2019;Faeth & Simberloff, 1981) and showed changes in disturbed habitats (Altamirano et al, 2016).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some studies have considered only the host plant richness and a linear positive relationship between host plant and galling insect richness was also found (Araújo, 2011;Souza et al, 2016). Moreover, in agreement with the high specificity of galling insects to their host plants (Carneiro et al, 2009), the specific composition of these insect communities has been closely related to floristic composition (Julião et al, 2017;Knuff et al, 2019). The proportion of plants damaged by phytophagous insects was also used as an herbivory indicator (Ekholm et al, 2019;Faeth & Simberloff, 1981) and showed changes in disturbed habitats (Altamirano et al, 2016).…”
Section: Introductionmentioning
confidence: 79%
“…In general, the studies assessing insect galling richness do not incorporate floristic composition, which may play an important role in shaping galling insect richness (Coelho et al, 2017(Coelho et al, , 2018Souza et al, 2016;Veldtman & McGeoch, 2003). For instance, the presence of the most frequently attacked plant life form by galling insect may modulate galling insect richness (Cuevas-Reyes et al, 2014;Gonçalves-Alvim & Fernandes, 2001;Knuff et al, 2019;Melo Júnior et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Box 1 (Continued) (Knuff, Staab, Frey, Helbach, & Klein 2019). Based on meta-analyses, ConFoBi researchers confirmed that crown-damaged trees improve nesting opportunities for cavity-nesting birds (Gutzat & Dormann, 2018) and that woodpeckers select cavitiesby relative rather than absolute tree size (Basile, Mikusinski, & Storch, 2020), but found that bird guilds are affected differently by forestry measures including retention, according to their life history, biome, and forest type .…”
Section: D2 Evidence-based Biodiversity Management Of Forestsmentioning
confidence: 98%
“…Preliminary results indicate positive overall effects of retention of structural elements for forest biodiversity but also high variability among taxa and landscape settings; further, our findings suggest high potential for optimizing the integration of retention into management practice. The first ConFoBi publications described technical and methodological advances for quantifying forest structures; for example, we found a high potential for optimizing the quality in reconstruction of 3D forest models from aerial images based on drones (Frey, Kovach, Stemmler, & Koch, ), showed how the abundance and diversity of tree‐related microhabitats can be predicted with readily available forest attributes (Asbeck, Pyttel, Frey, & Bauhus, ), recorded a lichen species new for Germany (Wirth, Tønsberg, Reif, & Stevenson, ), optimized the trap design to capture flying arthropods (Knuff, Winiger, Klein, Segelbacher, & Staab, ), and showed that the occurrence of specialist herbivore communities might be best explained by plant species composition rather than the abiotic environment (Knuff, Staab, Frey, Helbach, & Klein, ). Based on meta‐analyses, ConFoBi researchers confirmed that crown‐damaged trees improve nesting opportunities for cavity‐nesting birds (Gutzat & Dormann, ) and that woodpeckers select cavitiesby relative rather than absolute tree size (Basile, Mikusinski, & Storch, ), but found that bird guilds are affected differently by forestry measures including retention, according to their life history, biome, and forest type (Basile, Mikusinski, & Storch, ).…”
Section: Perspectives For Research and Conservationmentioning
confidence: 99%
“…Non-host stems and leaves can represent a physical barrier between the insect and the host (Perrin, 1976;Risch, 1981) and can disrupt visual cues and the background, reducing the probability that the galling insect will find its host (Castagneyrol et al, 2014;Muiruri et al, 2019). Although studies have demonstrated associations between plant diversity and gall abundance (Grossman et al, 2019;Knuff et al, 2019), the role of non-host tree abundance is still unclear in natural systems. As galling insects are very small insects, their flight is probably wind dependent (Jermy et al, 1988;Withers & Harris, 1997) and the physical disturbance of non-host individuals could have a strong impact on gall distribution regardless of species diversity.…”
Section: Introductionmentioning
confidence: 99%